Medication-Related Outcomes and Health Equity: Evidence for Pharmaceutical Care - Tamasine Grimes; Romaric Marcilly; Lorna Bonnici West; Maria Cordina (MDPI AG, 2023)
Marginalised people experience diminished access to pharmaceutical care and worse medication-related outcomes than the general population. Health equity is a global priority. This article explores the key evidence of health inequity and medication use, structures the causes and contributory factors and suggests opportunities that can be taken to advance the pharmaceutical care agenda so as to achieve health equity. The causes of, and contributors to, this inequity are multi-fold, with patient- and person-related factors being the most commonly reported. Limited evidence is available to identify risk factors related to other aspects of a personal medication use system, such as technology, tasks, tools and the internal and the external environments. Multiple opportunities exist to enhance equity in medication-related outcomes through pharmaceutical care research and practice. To optimise the effects and the sustainable implementation of these opportunities, it is important to (1) ensure the meaningful inclusion and engagement of members of marginalised groups, (2) use a person-centred approach and (3) apply a systems-based approach to address all of the necessary components of a system that interact and form a network as work processes that produce system outcomes.